Multiculturalism among Students in Madrasah: Knowledge, Challenges, and Social Capital - Syarif, Syarif; Abdullah, Faisal; Herlambang, Saifuddin (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2024)
Multicultural knowledge among students is essential to building diversity and harmony in social life. This study illustrates the importance of multiculturalism among students in fostering a sense of empathy, tolerance, cooperation, and social care in social interactions. In addition, this study also aims to analyze Muslim students’ knowledge about multiculturalism. Students’ knowledge about multiculturalism is presented based on information obtained through questionnaires and interviews. This research was conducted in West Kalimantan, with the data source being students, with 40 respondents from various ethnic backgrounds who were Muslim. The findings revealed that Muslim students’ knowledge is a social capital that impacts social life in West Kalimantan. The multicultural knowledge of Muslim students is manifested in two forms: cultural accommodation and cooperation in the field of culture and religion. A limitation of this study is that the data sources focus on Muslim students. The researcher suggested the need to collect data on students from non-Muslim backgrounds, thus the need to use more in-depth methods to gain a more comprehensive understanding of the case.